1999
DOI: 10.1159/000026596
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cholinergic Drugs on Neocortical EEG and Flash-Visual Evoked Potentials in the Mouse

Abstract: The effects of single intraperitoneal injection of two cholinesterase inhibitors, physostigmine (PHY; 0.01, 0.025, 0.05, 0.1, 0.2 mg/kg) and heptylphysostigmine (HEP; 0.5, 2, 6 mg/kg) on electroencephalographic (EEG) activity and flash visual evoked potentials (f-VEP) in the occipital cortex were compared in DBA/2 mice. EEG spectral analysis of awake periods showed that PHY at all doses and HEP at 2 mg/kg induced an increase of power in the 4.25- to 7-Hz frequency band. Furthermore, PHY at the higher doses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…1F, which shows the Wavelet power spectrum (see Materials and Methods) of the EEG as a function of time, just before, and following, lidocaine injection in the presence of halothane. The involvement of cholinergic pathways is also suggested by the fact that anticholinesterase drugs such as physostigmine produce slow type II theta oscillations in many species, including mice (23)(24)(25). We confirmed this in wild-type mice (n ϭ 3) and found that an i.p.…”
Section: Resultssupporting
confidence: 75%
“…1F, which shows the Wavelet power spectrum (see Materials and Methods) of the EEG as a function of time, just before, and following, lidocaine injection in the presence of halothane. The involvement of cholinergic pathways is also suggested by the fact that anticholinesterase drugs such as physostigmine produce slow type II theta oscillations in many species, including mice (23)(24)(25). We confirmed this in wild-type mice (n ϭ 3) and found that an i.p.…”
Section: Resultssupporting
confidence: 75%
“…These studies typically use auditory, visual or somatosensory stimuli and have primarily focused on early component responses (e.g. < 100msec) (see Mazzucchelli et al, 1995; Porciatti et al, 1999; Tebano et al, 1999; Frenkel et al, 2000; Troncoso et al, 2000; Metzger et al, 2007). More recent investigations extend that literature by providing evidence to suggest that several late ERP components, including a late positivity, can be obtained from mice that differ in their latencies, amplitudes, polarities and morphology depending on the recording site, and stimulus characteristics (see Ehlers & Somes 2002; Siegel et al, 2003; Umbricht et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The VEP waveform of rodents was first described in rats, defined by P1, N1, P2, N2, P3, and N3 peaks (21), and the mouse VEP also showed a similar response by flash stimulation (22) (Figure 2A). All fVEP responses of mice showed that the N1 wave and P2 wave were repeatable and stable in all mice, so we focused on the latencies of N1 and P2 and the peak-to-peak amplitude of N1-P2.…”
Section: Reliability Of Fvep Responses In Normal Micementioning
confidence: 76%
“…The requirements for recording pVEP in mice are high, while recording fVEP is simple and its waveform is easy to identify. Due to the different methods of recording and stimulation in different laboratories, the latencies and amplitudes of fVEP responses under different conditions (electrodes type, different stimulation intensities and rates, different anesthetic agents) may yield various parameters (5)(6)(7)19,21,22). We tested fVEP under the same experimental conditions and by the same operator to obtain stable and repeatable waveforms.…”
Section: Discussionmentioning
confidence: 99%